History of life - Cowen, Richard, 1940- (2013)
"This text is designed for students and anyone else with an interest in the history of life on our planet. The author describes the biological evolution of Earth's organisms, and reconstructs their adaptations to the life they led, and the ecology and environment in which they functioned. On the grand scale, Earth is a constantly changing planet, continually presenting organisms with challenges. Changing geography, climate, atmosphere, oceanic and land environments set a stage in which organisms interact with their environments and one another, with evolutionary change an inevitable result. The organisms themselves in turn can change global environments: oxygen in our atmosphere is all produced by photosynthesis, for example. The interplay between a changing Earth and its evolving organisms is the underlying theme of the book. The book has a dedicated website which explores additional enriching information and discussion, and provides or points to the art for the book and many other images useful for teaching. See: www.wiley.com/go/cowen/historyoflife"--
Machine generated contents note: Preface Chapter 1. The Origin Of Life on Earth Chapter 2. Earliest Life on Earth Chapter 3. Sex and Nuclei: Eukaryotes Chapter 4. The Evolution of Metazoans Chapter 5. The Metazoan Radiation Chapter 6. Changing Life in a Changing World Chapter 7. The Early Vertebrates Chapter 8. Leaving the Water Chapter 9. Tetrapods and Amniotes Chapter 10. Early Amniotes and Thermoregulation Chapter 11. The Triassic Takeover Chapter 12. Dinosaurs Chapter 13. The Evolution of Flight Chapter 14. The Modernization of Land and Sea Chapter 15. The Origin of Mammals Chapter 16. The End of the Dinosaurs Chapter 17. Cenozoic Mammals Chapter 18. Geography and Evolution Chapter 19. Primates Chapter 20. Evolving Toward Humans Chapter 21. Life in the Ice Age Index .
Includes bibliographical references and index.
Keywords: Paleontology; SCIENCE / Paleontology